O paradigma de sistema público de emprego da OIT e a sua construç\~ao histórica no Brasil - Sandro Pereira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– This study consists of an effort to analyze the process of constitution of the paradigm of the public employment system (SPE) in Brazil, having as a reference the programmatic model proposed from the deliberations of the International Labor Organization (ILO). Therefore, it is a matter of analyzing the relationship between two trajectories: the deliberative sequencing that established a propositional framework of articulated programs aimed at tackling the problem of unemployment; and the institutional sequencing of the formation of a Brazilian model of SPE. The approach used was intended to highlight the main institutional facts that led to this specific social protection system, which over time was detaching itself from the general social security system to have its own financing, coordination and operationalization arrangements. For this, it was verified how the decisions at the international level were received internally and how the Brazilian State was being instrumentalized, since the formation of a labor and social security institution in the 1930s until the consequences of the Federal Constitution of 1988 (CF/1988), to respond to commitments made over time.
Keywords: E65; H53; I39; J38; J23; 330; public employment system; International Labor Organization; Worker Support Fund; social policy; job market